Konversi Agama: Proses dan Faktor yang Mempengaruhi - Tisnawati, Tin; Winarno, Dwi; Rohimah, Siti (Lembaga Yasin AlSys, 2024)
This research aims to investigate the process of religious conversion and the factors that influence it. Religious conversion is a complex phenomenon involving fundamental changes in an individual's beliefs and identity. Through a qualitative approach, a literature review explores the causes, processes and factors that influence religious conversion. Data analysis was carried out using thematic methods. Research findings show that the religious conversion process involves stages such as search, consideration, religious experience, and decision making. Factors influencing religious conversion include social environmental influences, personal experiences, spiritual crises, search for meaning in life, and external factors such as mixed marriages or exposure to new cultures. The implications of this research can help our understanding of the dynamics of religious conversion and provide insight into intervention and guidance efforts in the context of religious diversity in society.